Reflectivity enhancement of full color tri-layer electrowetting display with polymer cholesteric liquid crystal films - Zhang, Beibei; Liao, Xiaoling; Xie, Lijuan; Tang, Biao; Zhou, Xin; Ye, Huapeng; Yuan, Dong (Frontiers in Physics, 2022)
Electronic paper display has received increasing attention due to its outstanding properties of wide viewing angle, bistable state and lower energy consumption. Among various electronic paper display technologies, electrowetting e-paper (EWD) is the most promising as it can achieve full-color display by using stacked layers or RGB color filter. However, the EWD is faced with several challenges, including poor color brightness, low contrast ratio and small color gamut. To improve the performance of the EWD, we proposed a new configuration of EWD consisting of three independent PCLC reflection films based on the cholesteric liquid crystal materials. We designed and experimentally fabricated three types of reflection films, and then added the PCLC films to the tri-layered EWD device. We experimentally characterized the reflectivity and color gamut of the sample in the dark room. It is found that the experimental results and simulation results match with each other. It is demonstrated that with the PCLC films, the reflectivity is improved by 20%, while the color gamut is improved by 80%, which is sufficient for the daily display demand of E-paper. The proposed EWD device containing PCLC reflection films provide a new strategy to improve the brightness and color gamut of current EWD device, and is promising for realizing the full-color E-paper display.